Functional recovery from sciatic nerve crush injury is delayed because of increased distal atrophy in mice lacking the p75 receptor. Issue 12 (17th August 2016) - Chen, Xiaojuan; Zhang, Jianguo; Wang, Xianjun; Bi, Jianzhong
Abstract : Peripheral nerve injuries are becoming more common, but without effective treatment, the outcome is often very poor. Recent research shows that p75 NTR plays an important role in nerve regeneration, but its mechanisms of action during behavioral recovery and axon regrowth remain unclear. To investigate these mechanisms, we examined recovery from sciatic nerve crush injury in wild-type and p75 NTR knockout mice. We found that sciatic nerve crush injury upregulates mRNA and protein expressions of p75 NTR and p75 NTR deficiency alters gene and protein expression of molecules associated with distal portion atrophy. However, p75 NTR deletion did not alter gene and protein expression in the spinal cord of molecules related to neuronal intrinsic growth capacity. Behavioral testing showed that functional recovery was delayed in mice lacking p75 NTR . These results suggest that p75 NTR regulates gene and protein expression that limits the distal atrophy after sciatic nerve injury, thereby regulating axonal growth and functional recovery.